THE EFFECT OF REINFORCING PANEL ZONE OF BOLTED END PLATE COLUMN BEAM CONNECTIONS - Yilmaz, Orkun; Bekiroglu, Serkan (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2016)
The aim of this study is to assess the efficiency of changing thickness of end plate and reinforcing panel zone in bolted end plate column-beam connections that are performed by finite element analyses under monotonic loading. In the first phase of the study, finite element analyses of two bolted end plate connections which were taken from literature were performed and the experimental results from the literature and the numerical results of the present study were compared. In the second phase, effects of increasing the end plate thickness and the effects of reinforcing panel zone of connections, taken from the literature, were investigated. To reinforce the panel zone, diagonal braces or column web doubler plates were used. Pretensioned bolts were used in connections and monotonic displacement loading are applied to end of cantilever beam. Material and geometry nonlinearities were considered in the analyses. The linear or nonlinear contacts between connection parts such as column, beam, bolt and plate were considered. Connections were evaluated in terms of loading capacity, moment - rotation curve, plastic strain distributions of panel zone and bolt tension forces. The results reveal that reinforcing panel zone causes the plastic strains of column panel zone to decrease but resulting in earlier buckling of beam flange and beam web and reductions in the rotational capacity of the connection.
Keywords: Bolted end plate connection; reinforcing panel zone; finite element analysis; nonlinear analysis; 3D SIMULATION; BEHAVIOR; Engineering